Development of Pop-Up Scrapbook Learning Media to Enhance Basic Literacy Skills in Children Aged 5–6 Years - Hijriah Hijriah; Kartini Marzuki; Herman Herman; Rika Kurnia R; Herlina Herlina (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This study aims to: (1) identify the need for developing pop-up scrapbook learning media to improve the basic literacy skills of children aged 5–6 years; (2) describe the design of pop-up scrapbook learning media for improving basic literacy skills of children aged 5–6 years; (3) examine the validity and practicality of pop-up scrapbook learning media; and (4) determine the effectiveness of pop-up scrapbook learning media in improving the basic literacy skills of children aged 5–6 years. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, observations, and questionnaires. The results show that: (1) the initial analysis indicates that children’s basic literacy skills are still relatively low, and teachers strongly support the development of innovative learning media to improve literacy skills among children aged 5–6 years; (2) the design of the pop-up scrapbook learning media was developed through several stages, including needs analysis, media production, preparation of a media user guide, teacher response questionnaires, and observation sheets for assessing children’s basic literacy skills; (3) the validation results from expert validators indicate that the pop-up scrapbook learning media is categorized as very valid and suitable for classroom implementation, while the practicality assessment by the Class B1 teacher places the media in the very practical category; and (4) the effectiveness test based on pre-test and post-test results demonstrates a significant improvement in children’s basic literacy skills after the implementation of the pop-up scrapbook learning media. Therefore, the developed media is considered highly effective for use in classroom learning to enhance the basic literacy skills of children aged 5–6 years.